Induction of immune response in goats immunized with Brucella melitensis 16M DNA - GUPTA, V K; ROUT, P K; CHANDRASEKHAR, T; VIHAN, V K (The Indian Journal of Animal Sciences, 2014)
The direct injections of B.melifensis DNA were given by intramuscular rout at different dose rates (0.5mg, 1.0mg and1.5 mg/animal) to 3 groups of goats, each group comprised 4 goats each. Two groups were kept as control (1 positive and1 negative). Three injections at 3-week intervals were given. The humoral immune response was analyzed every week (upto 5 week) and Iymphoproliferative response was analysed at 15th and 30th day after the last DNA injection. Humoralresponse measured 5 weeks post inoculation indicated that 1.0mg DNA injection leads to the generation of long-lived IgGresponses. Cellular immune response induced by the DNA was analyzed by studying T-cell response. Both 0.5 long and1.5mg DNA injection resulted in low specific T-cell proliferation in response to the Brucella melitensis extracts while 1.0mg DNA inoculated animals showed comparatively high T-cell proliferation. This specific induced proliferative responsewas also found at 30 day postinoculation.